2015
DOI: 10.3109/14397595.2015.1054081
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of 124 patients with polymyositis and dermatomyositis: Statistical analysis of prognostic factors

Abstract: Our study indicates that when age of onset and serum ferritin are used in combination, we can predict prognosis of patients with PM/DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 22 publications
3
15
1
Order By: Relevance
“…Statistical analysis was performed using Graph Pad Prism 5 (San Diego, CA, USA) and EZR software (Kanda 2013), as previously described (Ishizuka et al 2016;Yoshida et al 2016). The Fisher's exact test was used for binary data, and the Mann-Whitney U-test was used for continuous data.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed using Graph Pad Prism 5 (San Diego, CA, USA) and EZR software (Kanda 2013), as previously described (Ishizuka et al 2016;Yoshida et al 2016). The Fisher's exact test was used for binary data, and the Mann-Whitney U-test was used for continuous data.…”
Section: Discussionmentioning
confidence: 99%
“…The Fisher's exact test was used for binary data, and the Mann-Whitney U-test was used for continuous data, as previously described (Tomiyama et al 2016). The Kaplan-Meier method was used to estimate the retention rate of ABT, and the log-rank test was used to calculate p values (Ishizuka et al 2016;Yoshida et al 2016). Multivariate logistic regression analysis was used to identify factors that were associated with discontinuation of ABT.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, reliable biomarkers are needed to guide the treatment [20]. Several studies have shown association between serum ferritin and disease severity in various inflammatory disorders including renal involvement in SLE and interstitial lung disease in dermatomyositis [13,14]. Therefore, some authors suggest use of more intensive treatment in newly diagnosed dermatomyositis patients with high serum ferritin levels [13].…”
Section: Discussionmentioning
confidence: 99%
“…Role of serum ferritin as a marker of disease activity and involvement severity has already been shown in sepsis, graft rejection, dermatomyositis and SLE; however, it has not been previously studied in vasculitides [10][11][12][13][14]. Herein, we aim to investigate association of serum ferritin level with activity and severe manifestations of disease in patients with GPA.…”
Section: Introductionmentioning
confidence: 99%